Audit Quality and Its Impact on Financial Reporting Transparency - Darmawan, Aliya (Golden Ratio of Auditing Research, 2023)
This qualitative research study investigates the intricate relationship between audit quality and financial reporting transparency within the corporate governance landscape. Drawing on principles of grounded theory, the research aims to explore the interplay, determinants, and implications of this relationship informed by existing literature. Through systematic document analysis of academic articles, regulatory documents, and scholarly publications, key dimensions and determinants of audit quality and financial reporting transparency are identified and analyzed. The study reveals that audit quality is influenced by factors such as auditor tenure, audit firm size, auditor industry specialization, and audit fees, each playing a nuanced role in shaping the effectiveness and reliability of audits. Similarly, financial reporting transparency is influenced by regulatory frameworks, theoretical perspectives, and technological advancements, highlighting the multifaceted nature of transparency mechanisms and drivers. The findings underscore the critical role of audit quality in enhancing financial reporting transparency, emphasizing the importance of auditor independence, competence, and ethical conduct. Moreover, the study highlights the interconnectedness of audit quality, financial reporting transparency, and corporate governance, with effective governance mechanisms serving as critical determinants of both audit quality and transparency outcomes. The research contributes to the understanding of the complex dynamics shaping audit quality and financial reporting transparency, providing valuable insights for stakeholders in the auditing profession and corporate governance.